Penguatan Toleransi dan Moderasi Beragama melalui Pendekatan Edukasi Program Kerja KKN UINSU di Desa Kineppen Kabupaten Karo : (Studi Komparatif Nilai-nilai Islam Dan Budaya Lokal) - Rizal Lubis; Benni Icshanda Rahman; Saif Arrasid; Adelia Sahputri Nainggolan; Mhd. Arif Lubis; Uzlah Hansel Bahrin HSB (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to strengthen religious tolerance and moderation in Kineppen Village, Karo Regency, through an educational approach in the implementation of the Community Service Program (KKN) at the State Islamic University of North Sumatra (UINSU). The background of the study stems from the condition of religious diversity in the village, which demands the presence of a moderate and tolerant attitude to create sustainable social harmony. The method used is a qualitative case study approach, where data is obtained through in-depth interviews with community and religious leaders, participatory observation of interfaith activities, and documentation of various educational activities during the KKN program. The results show that KKN students carried out various educational activities such as interfaith dialogue, counseling on the value of tolerance, and participation in joint religious events that functioned as a means of building collective awareness. These activities have been proven to increase community understanding of the importance of a moderate attitude in religion, strengthen communication between residents, and strengthen social ties amidst diversity. Furthermore, this KKN program also created a more inclusive interaction space, thereby reducing the potential for social friction that may have previously arisen due to differences in belief. Thus, the educational approach in KKN UINSU can be seen as an effective strategy for fostering religious tolerance and moderation in a multicultural society. The findings of this study imply that similar programs can be replicated and developed in other regions with similar diversity dynamics to maintain social harmony and strengthen national unity.